2009
DOI: 10.1111/j.1939-1676.2009.0330.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cardiac Troponin I Concentrations in Cattle with Cardiac and Noncardiac Disorders

Abstract: Background: Making a clinical diagnosis of pericarditis in cattle is difficult and additional diagnostic tests are needed to evaluate cattle with suspected pericarditis. Serum cardiac troponin I (cTnI) concentrations are increased in cattle with pericarditis, but the utility of measuring serum cTnI concentrations in cattle with suspected pericarditis in cattle remains unclear.Objectives: To determine if serum cTnI concentrations in cattle can be used to differentiate pericarditis from other cardiac disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…Cardiac injury in cattle has been identified by increased cardiac troponin levels in a variety of diseases that include monensin toxicosis (Varga et al, 2009), traumatic reticulopericarditis (Gunes et al, 2008;Mellanby et al, 2009), footand-mouth disease (Gunes et al, 2005;Karapinar et al, 2010), and endotoxaemia (Peek et al, 2008). The cardiospecific isoenzyme troponin I provides the most sensitive and specific indication of cardiac necrosis whereas the predictive value of serum CK and LDH activities is much lower (Radostits et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac injury in cattle has been identified by increased cardiac troponin levels in a variety of diseases that include monensin toxicosis (Varga et al, 2009), traumatic reticulopericarditis (Gunes et al, 2008;Mellanby et al, 2009), footand-mouth disease (Gunes et al, 2005;Karapinar et al, 2010), and endotoxaemia (Peek et al, 2008). The cardiospecific isoenzyme troponin I provides the most sensitive and specific indication of cardiac necrosis whereas the predictive value of serum CK and LDH activities is much lower (Radostits et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several recently published studies have reported blood cTn I concentration from cattle having cardiac and non-cardiac intra-thoracic diseases [23][24][25][26][27]31]. These reports included pericarditis, endocarditis, congenital heart disease, monensin toxicity, endotoxemia, reticulitis, mediastinal abscess, thymic lymphoma, caudal vena cava thrombosis, and chronic suppurative pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Elevações nas concentrações séricas foram menores em quadros de arritmias causadas por lesões miocárdicas secundárias (Nath et al, 2012). Lesões isquêmicas crônicas induzidas no miocárdio de ovinos igualmente resultaram elevações de cTnI, Em bovinos, Mellanby et al (2009) verificaram o aumento sérico da cTnI em casos de pericardite e embora tenha indicado lesão miocárdica não permitiu a confirmação da etiologia.…”
Section: Uso Da Troponina Como Marcador De Doenças Cardíacas Primáriasunclassified